Diritto alla salute e “ciclo del farmaco” nel prisma dei principi costituzionali (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Starting from the legal regime of drugs in the perspective of the constitutional right to health, the contribution discusses the life cycle of medicinal products: from scientific research and the clinic from scientific and clinic research until the drug is placed on the market. Particular attention is given to two important figures in the cycle: the attending physician and the pharmacist; as well as the essential right to access pharmaceutical treatments.
Keywords: Freedom of research; pharmaceutical experimentation; price of medicines; pharmaceutical profession; access to medicines